2021
DOI: 10.1177/1934578x211016643
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Ingredients and Mechanisms of Curcumae Radix for Depression Based on Network Pharmacology and Molecular Docking

Abstract: Background Curcumae Radix (CR), derived from the dry roots of Curcuma longa L., family Zingiberaceae, is widely used to treat depression. However, the ingredients and mechanisms of CR are still unclear. The purpose of this study was to solve this problem using network pharmacology and molecular docking. Methods The active ingredients of CR were screened through TCMSP, and the depression-related genes were obtained through the Genetic Association, GeneCards, and OMIM databases. Then, DisGeNET score was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Cavity-detection guided blind docking (CB-Dock, http://clab.labshare.cn/cb-dock/php/index.php) was used to perform molecular docking between TFRD ingredients and key proteins in the identified pathway (AKT: PDB ID 1UNP, HIF-1α: PDB ID 4H6J, VEGF: PDB ID 1MKK) to evaluate the binding potential between TFRD active ingredients and proteins (Liu et al, 2020). CB-Dock integrates the docking program AutoDock Vina to predict the binding of the protein to the ingredients, with an accuracy rate of 70% (Wang et al, 2021).…”
Section: Ingredient Verification and Potential Pathway Screeningmentioning
confidence: 99%
“…Cavity-detection guided blind docking (CB-Dock, http://clab.labshare.cn/cb-dock/php/index.php) was used to perform molecular docking between TFRD ingredients and key proteins in the identified pathway (AKT: PDB ID 1UNP, HIF-1α: PDB ID 4H6J, VEGF: PDB ID 1MKK) to evaluate the binding potential between TFRD active ingredients and proteins (Liu et al, 2020). CB-Dock integrates the docking program AutoDock Vina to predict the binding of the protein to the ingredients, with an accuracy rate of 70% (Wang et al, 2021).…”
Section: Ingredient Verification and Potential Pathway Screeningmentioning
confidence: 99%
“…14 In addition, we previously discovered 5 ingredients of Curcumae Radix through TCMSP and found that the depression-related protein PTGS2 has good binding activity to oxycurcumenol through molecular docking, which may have an antidepressant effect through calcium, estrogen, PI3K-Akt, and ErbB signaling pathways. 15 Therefore, in this study, 8 active ingredients of Cattail Pollen were screened according to their pharmacokinetic properties through the TCMSP database, namely naringenin, arachidonic acid, isorhamnetin, β-sitosterol, kaempferol, testosterone palmitate, kaempferol-3-O-α-L-rhamnosyl(1→2)-β-D-glucoside, and quercetin. We hypothesize that these active ingredients of Cattail Pollen can reduce the occurrence of infertility by combining with the hub proteins of differential gene regulation in patients with endometriosis-related infertility, which are reported as follows.…”
Section: Introductionmentioning
confidence: 99%